Emotion in Christian and Islamic Contemplative Texts, 1100–1250 - Lazikani, A. S. author. aut Link
XVII, 271 p.
Keywords: This book offers a comparative study of emotion in Arabic Islamic and English Christian contemplative texts, c. 1110-1250, contributing to the emerging interest in ‘globalization’ in medieval studies. A.S.Lazikani argues for the necessity of placing medieval English devotional texts in a more global context and seeks to modify influential narratives on the ‘history of emotions’ to enable this more wide-ranging critical outlook. Across eight chapters, the book examines the dialogic encounters generated by comparative readings of Muhyddin Ibn ‘Arabi (1165-1240), ‘Umar Ibn al-Fārid (1181-1235), Abu al-Hasan al-Shushtarī (d. 1269), Ancrene Wisse (c. 1225), and the Wooing Group (c. 1225). Investigating the two-fold ‘paradigms of love’ in the figure of Jesus and in the image of the heart, the (dis)embodied language of affect, and the affective semiotics of absence and secrecy, Lazikani demonstrates an interconnection between thereligious traditions of early Christianity and Islam.